Sleep quality is associated with aggression in forensic psychiatric patients, independent of general psychopathology. Issue 5 (2nd September 2020) - Van Veen, Maaike M.; Karsten, Julie; Verkes, Robbert-Jan; Lancel, Marike
ABSTRACT: Several studies found associations between poor sleep quality and aggression in general and (forensic) psychiatric populations. Both poor sleep and aggression have been related previously to general psychopathology, but studies rarely have addressed this possible confounding factor appropriately. The current study aimed to replicate the association between sleep quality and aggression in a forensic psychiatric sample, including adjustment for psychopathology. We used cross-sectional data from an observational study in forensic psychiatric inpatients (n = 166). Poor sleep quality was significantly associated with higher self-reported aggression, independent of general psychopathology. Poor sleep quality accounted for a substantial part of the variance in aggression. This was observed for self-reported physical aggression, verbal aggression, anger, and hostility, all showing relations with poor sleep quality that were not better accounted for by general psychopathology. Poor sleep quality was related to higher clinician-rated hostility as well, however, this association was weak and the explained variance low. These results confirm and substantiate previously found associations between sleep quality and aggression in forensic psychiatric patients. They highlight the importance of targeting sleep problems as part of the treatment of psychiatric patients with disruptive behavior and encourage further research aimed at unraveling the relation between sleep and aggression.